Leverage and Risk Taking under Moral Hazard - Christian Hott (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2013)
This paper examines the impact of implicit guarantees and capital regulations on the behavior of a bank and on the expected losses for its depositors. I show that implicit guarantees increase the incentives of the bank to enhance leverage and/or risk taking and that this leads to higher expected losses for its depositors. To reduce the adverse effects of moral hazard, policy measures have to be taken. However, a simple leverage ratio is likely to increase expected losses further and risk adjusted capital requirements do not necessarily affect highly leveraged banks with very low risk assets. A combination of both requirements can be successful. Positive long-term effects can be achieved by a reduction of moral hazard and informational imperfections. However, it is difficult to achieve these reductions and potentially severe short-term effects have to be taken into account.
Keywords: G18; G21; G32; 330